Did Collagen Cross-Linking Reduce the Requirement for Corneal Transplantation in Keratoconus? The Canadian Experience. Issue 11 (November 2019) - Sklar, Jaime C.; Wendel, Colten; Zhang, Angela; Chan, Clara C.; Yeung, Sonia N.; Iovieno, Alfonso
Abstract : Purpose: To investigate the relationship between corneal collagen cross-linking (CXL) and the number of corneal transplants required for the treatment of keratoconus (KCN) in 2 major Canadian provinces. Methods: This is a retrospective review of all corneal transplantation performed in Ontario and British Columbia over an 18-year period (1998–2016). Data were collected at the Eye Bank of Canada—Ontario/British Columbia Divisions. The primary outcome was to determine the change in proportion and absolute number of corneal transplants required for treatment of KCN since the introduction of CXL in Canada in 2008. Results: A total of 31, 943 grafts were included. Overall, the mean age of participants was 39.3 ± 2.2 years, with our cohort being composed of 28% of women and 72% of men. The results showed a significant decrease in the proportion of total transplants required for KCN between 1998 and 2016 [1998–2008 (pre-CXL), range: 14.77%–12.63%; 2009–2016 (post-CXL), range: 12.98%–5.50%, P < 0.001]. However, there was no change in the absolute number of grafts performed for KCN over this time (pre-CXL: 179 ± 26 grafts; post-CXL: 198 ± 27 grafts; P = 0.5), whereas the total number of grafts (pre-CXL: 1318 ± 183 grafts; post-CXL: 2181 ± 404; P < 0.001) and endothelial keratoplasties (pre-CXL: 59 ± 108; post-CXL: 966 ± 431 grafts; P < 0.001) increased significantly. In addition, there were no changes in penetrating keratoplasty/deep anterior lamellar keratoplasty (DALK) performed for indications other than KCN (pre-CXL: 1080 ± 157; post-CXL: 1017 ± 92; P > 0.5). Conclusions: Although there has been a significant decrease in the proportion of corneal graft rates for KCN since the introduction of CXL as a factor of all transplants performed for all indications, this result is most likely because of an increase in endothelial keratoplasties rather than decreased transplants performed for definitive treatment. Abstract : Supplemental Digital Content is Available in the Text.